Protect Labour Rights and Promote Safe Working environment (Journal of Pedagogical Inventions and Practices, 2022)
The achievement of the 17 Sustainable Development Goals approved by the UN General Assembly will depend on whether or not the goal 8, Decent works and economic development; goal 8.8, protect labour rights and promote safe working environment. This paper discusses the meaning of Sustainable Development and how it is different from sustainability. Also, the paper discusses about the labour rights, safe working conditions and ways to promote it. The last section of the paper discusses about the two indicators of the goal 8.8 which are fatal and non fatal occupational injuries and migrant workers. Both of which have huge implications on SDG’s goals. Without human resource no goal can be achieved, hence it is important to protect labour rights and provide safe working environment to all the workers, including migrant workers, in particular women migrants, and those in precarious employment. Employees are drawn to a workplace that is devoid of injuries and accidents. Employees are more happy and productive when they work in a safe setting. For both companies and employees, safe working conditions are essential. Employees have a right to a safe working environment. Objectives: In order to accomplish economic progress, it is critical to defend workers' rights and provide a safe working environment. Human casualties have difficult to quantify effects, yet they can have serious ramifications for the employees' families. As a result, the paper emphasizes the need of a safe working environment, as well as the capabilities of the federal and state governments to regulate employee interests, establish a safe workplace, and expand job prospects.